High parasite burden increases the surfacing and mortality of the Manila clam (Ruditapes philippinarum) in intertidal sandy mudflats on the west coast of Korea during hot summer - Ki-Woong Nam; Hee-Do Jeung; Jae-Hee Song; Kwan-Ha Park; Kwang-Sik Choi; Kyung-Il Park (Parasites & Vectors, 2018)
Abstract Background Over the past few decades, mass mortality events of Manila clams have been reported from several tidal flats on the west coast of Korea during hot summers. During such mortality events, once clams simultaneously surface, they fail to re-burrow, perishing within a week. The present study aimed to identify the possible causes of the mass mortality of this clam species by investigating the Perkinsus olseni parasite burden and immune parameters of surfaced clams (SC) and normal buried clams (NBCs) when sea water or sediment temperature in the study area varied from 25 °C to 34 °C from late July through mid-August 2015. Results We collected 2 groups of clams distributed within a 10-m2 area when a summer clam mortality event occurred around Seonyu-do Island on the west coast of Korea in 2015. The clams were collected 2 days after they surfaced on the sediment and still looked healthy without any gaping. The clams were transported to the laboratory, and we compared P. olseni infection intensity and cell-mediated hemocyte parameters between the NBCs and SCs. SCs showed significantly higher levels of P. olseni burden, lower condition index, and lower levels of cell-mediated immune functions than those of NBCs. Conclusions Our study suggests that high P. olseni infection weakens Manila clams’ resistance against thermal stress, causing them to surface. We surmise that the summer mass mortality of Manila clams on the west coast of Korea is caused by the combined effects of high P. olseni infection levels and abnormally high water temperature stress.